Magnetic fields and polarization in AGN jets - Wardle John F. C. (EPJ Web of Conferences, 2013)
In the literature there is now a wealth of images of AGN in both linear and circular polarization at milliarcsecond resolution of many sources at multiple epochs and wavelengths. This review is a broad overview of our current state of knowledge of the polarization properties of AGN jets, and of what we can infer about the structure of their magnetic fields and the distribution of Faraday rotating material, and also what is premature to infer. We suggest that while many of the observations of transverse rotation measure gradients may be correct, they have in general been observed with neither enough resolution nor sensitivity to be incontrovertible. Fortunately, this could be remedied using the new broad-band receivers on the VLBA. We also argue that while a transverse rotation measure gradient is a strong indicator of a toroidal component of magnetic field, it does not necessarily imply a helical magnetic field. In jets where the dominant field component appears to be parallel to the jet, it more likely consists of sheared loops or compressed random fields that are not vector ordered. Finally, we draw attention to the power of imaging in all four Stokes parameters at multiple frequencies to constrain the three-dimensional magnetic field structure and the particle content of jets and measure fundamental physical properties.